Integrasi Al-Quran pada Mata Pelajaran Matematika terhadap Kemampuan Siswa - Fenny Anggreni (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2019)
The purpose of Education in Indonesia is to develop students' abilities in various aspects, both in the areas of cognitive ability and religious ability. One of the efforts to fulfil that goal is by integrating general science with religious knowledge. An example of this Integration is to associate mathematics with the Quran. The reason behind this integration is that the contents of the Qur'an cover many of the symbols of numbers and meanings that are also part of mathematics. This integration is also applied to educational institutions in Indonesia. It's just a bit of research done to integrate mathematics education with the Quran to improve students' ability in Indonesia as well as in Aceh, especially Aceh Tamiang who have never done the research. Related to existing literature gaps so this study was conducted to analyze how the integration of the Qur'an on mathematics subjects on students' ability in MTs Aceh Tamiang. This type of research uses quantitative research with an experimental approach, its design research uses a One-shot case study design, the instrument uses a test. The results show that the application of the Qur'an in mathematics subjects at MTs Aceh Tamiang is said to be good because students are above average. It is therefore advisable for other schools to apply the Qur'an in mathematics subjects.